Prediksi Penjualan Menggunakan Algoritma Regresi Linear pada Koperasi Karyawan Usaha Bersama - Muhamad Galih; Prima Dina Atika; Mukhlis (Journal of Informatic and Information Security, 2022)
Koperasi Karyawan Usaha Bersama is one of the cooperative that has minimarket as one of their business strategy that sales a lot of goods people need. The amount of item sold every day is sometimes uncertain. There is a day when a lot of things are sold on that day, and there is also a day when there are only a few stuff are sold. The purpose of this study is to do prediction the sales of goods sold every day. With this prediction result, the minimarket can determine and choose what strategies are the best to maximize their profit. We use Linear Regression to do this study with CRISP-DM as the model process. The result of the analysis that uses data from March to April 2022 shows that MAPE has the better result with 10.7% compared to RMSE with 42.091.